%@Auteur:Thierry Joffredo\par Transforme ces différences en produits en utilisant la formule $k\times(a-b)=k\times a-k\times b$: \begin{itemize} \item[$\bullet$] $5\times14-5\times7=5\times(\ldots\ldots-\ldots\ldots)$ \item[$\bullet$] $113\times1,5-113\times0,8=\ldots\ldots\times(\ldots\ldots-\ldots\ldots)$ \item[$\bullet$] $25\times17-12\times17=(\ldots\ldots-\ldots\ldots)\times\ldots\ldots$ \item[$\bullet$] $5\times11,2-11,2\times1,4=\ldots\ldots\times(\ldots\ldots-\ldots\ldots)$ \end{itemize}